Deverbal adjectives at the interface : a crosslinguistic investigation into the morphology, syntax and semantics of -ble - Oltra Massuet, Maria Isabel (Interface explorations ;, 2013)
This volume explores the syntactic, semantic and morphological properties of -ble adjectives from a comparative perspective within Distributed Morphology. The proposal implicates a number of central issues in the syntax-semantics-morphology interface, e.g. cross-category derivations, verb classification, locus of linguistic variation, or status of impossible words. The volume also contributes novel empirical data, which are analyzed in the light of a previously unnoticed correlation between Spanish and English.